Effect of Ethanol Extract of Hedyotis Diffusa Willd on Inhibiting Lymphangiogenesis in Colorectal Cancer - Lihui WEI; Minghe LIN; Hong YANG; Lumin LIN; Jun PENG; Jiumao LIN (康复学报)
Objective:To evaluate the effect of Ethanol Extract of Hedyotis Diffusa Willd (EEHDW) on lymphangiogenesis in colorectal cancer (CRC) in vitro, and to investigate the underlying mechanisms.Methods:SW620 cells were received different concentration of EEHDW for a certain period of time. MTT assay was used to evaluate cell ability. Cell migration was detected by Wound Healing. And the VEGF-C and VEGF-D in the cytoplasm expression was examined by Western Blot. Human lymphatic endothelial cells (HLEC) were treated with different concentration of EEHDW for a certain time-point. Cell viability was examined by MTT assay and cell morphology was observed by phase-contrast microscope. Cell survival was estimated by colony formation assay. Cell apoptosis and proliferation were detected by AnnexinⅤ/PI staining and cell cycle were measured by flow cytometry (FCM). Cell migration was evaluated by transwell assay. Lymphatic vessel formation ability was examined by tube formation assay.Results:MTT assay showed that EEHDW could remarkably decrease the viability of SW620 cells in dose-dependent. Wound healing assay showed that EEHDW inhibited the migration of SW620 cells. Western Blot suggested that EEHDW could reduce the expression level of VEGF-C and VEGF-D in the cytoplasm. MTT assay and colony formation assay showed that different concentration of EEHDW could reduce the viability and survival of HLEC. Phase-contrast microscope, cell DNA content, AnnexinⅤ/PI staining showed that EEHDW did not have significant effect on cell morphological, cell cycle, and cell apoptosis. Transwell assay and Tube formation assay showed that EEHDW remarkably suppressed cell migration and lymphatic vessel formation in a dose-dependent manner.Conclusion:EEHDW can inhibit the activation of VEGF-C and VEGF-D, which is one of the most important mechanisms to inhibit lymphangiogenesis and migration in colorectal cancer.